PENGARUH BELAJAR MEMBACA TERHADAP KECAKAPAN BERCERITA ANAK TK AL-DJUFRI III DESA BLUMBUNGAN KECAMATAN LARANGAN KABUPATEN PAMEKASAN TAHUN PELAJARAN 2021/2022 - Sri Agustina; M Ridlwan; Ratno Abidin (Universitas Muhammadiyah Surabaya, 2022)
The purpose of this study was to determine the effect of learning to read on storytelling skills for children in Al-Djufri III Kindergarten, Blumbungan Village, Larangan District, Pamekasan Regency, 2021/2022. Learning to read needs to be built from an early age with a variety of creativity that supports it, Â whether doneÂ withinÂ the family or the environment. children's Â study area. The research method used in this study uses quantitative methods. With convincing quality, explanations regardingÂ researchÂ resultsÂ canÂ only be relatedÂ toÂ those inÂ the research. DesignÂ inÂ quantitative researchÂ includes determiningÂ the subject from which information or data can be obtained, the techniques used in data collection, as well as the procedures taken for collection, and the treatment that can be carried out (especially for experimental research). the results of the research that the author did through questionnaire methods can be concluded that kindergarten children. AL-DJUFRI III Â which Â is Â located Â in Â Blumbungan Â Village, Â Larangan Â District, Â Pamekasan Â Regency Â for Â the 2021/2022 Academic Year with efforts to learn to read for children can increase storytelling interest.Â Keywords: questionnaire; quantitative; subject; experimental